2022
DOI: 10.1007/s10198-022-01434-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the PAM-13 instrument in the Hungarian general population 40 years old and above

Abstract: Background Patient activation comprises the skills, knowledge and motivation necessary for patients’ effective contribution to their care. We adapted and validated the 13-item Patient Activation Measure (PAM-13) in the ≥ 40 years old Hungarian general population. Methods A cross-sectional web survey was conducted among 900 respondents selected from an online panel via quota sampling. After 10 days, the survey was repeated on 100 respondents. The distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…The Rasch analysis results and the multiple-group SEM with the same configuration suggest that the PAM-13 is a single underlying factor across YA cancer survivors during and after treatment. The unidimensional structure of the scale has been observed in the original study by Hibbard et al [ 11 ] that dealt with the original version and other studies that dealt with other language versions [ 12 , 13 ]. The results of McDonald’s omegas and item-total correlations supported the good internal consistency of the PAM-13 across YA cancer survivors during and after treatment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The Rasch analysis results and the multiple-group SEM with the same configuration suggest that the PAM-13 is a single underlying factor across YA cancer survivors during and after treatment. The unidimensional structure of the scale has been observed in the original study by Hibbard et al [ 11 ] that dealt with the original version and other studies that dealt with other language versions [ 12 , 13 ]. The results of McDonald’s omegas and item-total correlations supported the good internal consistency of the PAM-13 across YA cancer survivors during and after treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Existing studies have confirmed the original and other language versions of PAM-13 as a unidimensional scale that indicates the degree of activation that helps chronically ill individuals become fully engaged in managing their health [ 11 13 ]. Furthermore, the studies validated the scale for application in individuals with various chronic conditions (e.g., arthritis, hypertension, chronic pain, kidney disease, and diabetes) [ 11 , 14 16 ] and for the general population [ 12 ]. Previous studies commonly reported that among the participants, demographic characteristics (e.g., older age and lower educational level), health condition (e.g., depression, fatigue, and poor quality of life), and lower self-efficacy on controlling for disease and symptom were negatively related to the score of PAM-13 [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scarce use of the “strongly disagree” category has also been noted in other PAM-13 studies [ 19 , 21 , 23 , 31 , 41 ], and the presence of ceiling effects is a widespread phenomenon (e.g., 18, 20, 23, 36, 79, 104, 106). It is noteworthy, however, that some studies did not observe any item ceiling effects [ 24 , 26 , 79 , 107 ], which might be attributed to the specific cultural background of the population, the age groups considered or the type of disease under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Data analyses presented here adhered to the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) best practice guidelines for patient-reported outcome measures [ 51 , 52 ]. We applied methods from both classical test theory (CCT) and item-response theory (IRT) to ensure comparability to previous PAM-13 validation studies [ 18 , 19 , 24 , 40 ] and to explicitly model the relationship between an individual’s trait level and their likelihood of providing particular responses to specific items [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation